Comparison of cardiorespiratory effects of terbutaline and salbutamol aerosols in patients with reversible airways obstruction. Issue 5 (September 1973) - Harris, Luke
Abstract : Harris, L. (1973). Thorax, 28, 592-595. Comparison of cardiorespiratory effects of terbutaline and salbutamol aerosols in patients with reversible airways obstruction. The effects of pressurized aerosol administration of terbutaline were compared with those of salbutamol in 14 patients with at least 20% reversibility of airways obstruction. The two drugs were found to be equipotent bronchodilators in the dosage used. Salbutamol was found to produce significant increases in minute ventilation, physiological dead space/tidal volume ratio, and ventilatory equivalent for oxygen, with significant falls in arterial oxygen tension and heart rate. Terbutaline did not induce significant changes in any of these variables. These results suggest that terbutaline is less likely than salbutamol to have an adverse effect upon ventilation-perfusion relationships.